A synthesis of policy issues and recommendations towards enhancing access to and utilization of agricultural genetic resources for climate-change adaptation in East Africa: Report of a Regional Policy Workshop, 1-2 April 2021, Kisumu, Kenya - Otieno, Gloria Atieno; Recha, Tobias; Fadda, Carlo; Vernooy, Ronnie; Halewood, Michael; Spellman, Olga (2021)
Climate change negatively affects farmers’ production systems and leads to loss of genetic diversity. One key climate-change adaptation strategy is for farmers to sustainably use a broader range of crops and varieties that are either better adapted to their planting context or that will buffer against excessive crop losses as a result of unpredictable climate events and (resulting) pest and disease outbreaks. Accessing a wider range of genetic resources from different sources is also especially important to aid in the development of new traits for climate-change adaptation. Publicly managed genebanks are one of the main sources of this diversity. Access to genetic resources from these genebanks is available through the Multilateral System (MLS) of Benefit Sharing Fund (BSF) of the International Treaty for Plant Genetic Resources for Food and Agriculture (ITPGRFA). Through this system, genetic resources for research and breeding purposes are pooled and accessed using the Standard Material Transfer Agreement (SMTA). Through several research projects in East Africa, the Alliance of Bioversity International and CIAT has carried out participatory research with farmers in Ethiopia, Kenya, Tanzania and Uganda using durum wheat, sorghum, finger millet and beans from the national genebanks. Farmers and breeders have selected the best performing varieties with important traits for climate-change adaptation. Some of these varieties are potential candidates for breeding programs, while others were so good that farmers prefer to use them directly. However, the SMTA does make provisions for the direct use and commercialization of materials exchanged through the MLS; circumnavigating this issue has been the main focus of the Regional Policy Workshop.This workshop brought together stakeholders from the national genebanks, policymakers, farmer organizations and private sector actors to deliberate on the key challenges related to the direct use and commercialization of these varieties, and to explore the various options for seeking permission from providers for their direct use and commercialization in accordance with their national regulations.